O lugar da física na formação dos professores de ciências naturais da rede escolar pública municipal de Uberlândia - Silva, Alexandre Leite dos Santos (2015)
This research has had as a purpose to comprehend how the physics knowledge has been and is built in the formation of Natural Science teachers, graduated in Biological Sciences, from the municipal public school system in Uberlândia, Minas Gerais. This purpose have relation with understanding that teaching of Physics in the final years of the elementary school has been strategic to the education and development of the country, and the quality of this schooling depends on the formation of the Natural Science teacher. To development of investigation, the conception of teaching knowledge adopted is based in studies of Maurice Tardif. This point of view, the teaching knowledge is plural and temporal, coming in through of several sources and built in all time of life of the teacher, and not alone in your initial traning in the college. For this reason, within a qualitative approach, it has been used Robert Yin s methodology to case study research, with three Natural Sciences teachers, through data collected by semi structured interviews, questionnaires, electronic messages and documents. To the data analysis it has been adopted the categorical analysis and data triangulation to the construction of the explanation. The data interpretation has shown that the construction of the physics knowledge of the research subjects has happened especially in High School and not during the initial training. In the professional practice, its physics apprenticeship has been performed through textbooks and internet.